Strategic Synergies: ESG Performance, Political Connection, and Audit Committees in Enhancing Company Value - Septiani, Dwi; Munandar, Agus (The Indonesian Journal of Accounting Research, 2025)
This study examines the impact and implications of Environmental, Social, and Governance (ESG) performance, political connections, and audit committees on firm value in companies listed on the Indonesia Stock Exchange for the 2019–2023 period, with a total sample of 90 observations. The study employs a panel data regression method using the weighted least squares (WLS) model. The findings indicate that ESG performance and audit committees have a positive and significant effect on firm value, while political connections negatively impact firm value. This study is expected to encourage the adoption of good ESG practices and audit committee governance while also serving as a consideration for companies in evaluating the cost-benefit of political connections. Future research is recommended to expand the sample size, use ESG data from multiple sources, examine the individual effects of ESG pillars, conduct studies in other developing countries, and explore alternative firm value measurements and qualitative approaches.